The Idea of Privatization and Self-Financing of Prison Management in Positive Law and Islamic Law - Herlambang, Herlambang; Pradityo, Randy; Rahmasari, Helda; Eryke, Herlita; Putra, Yagie Sagita (AL-ISTINBATH : Jurnal Hukum Islam, 2024)
This research aims to explore the basics of the idea of abolishing criminal justice in Indonesia and possible alternative solutions to problems that arise in prisons, especially from a theoretical perspective and comparison with Islamic law and customary law. The legal research method in this research is normative (doctrinal), research activities carried out include inventorying, explaining, interpreting and systematizing and broadcasting all Islamic law and customary law, which are related to the idea of abolishing prison sentences. The results of the research show that imprisonment is not recognized in the Islamic view, whereas currently imprisonment is acceptable only as long as the punishment provides a lot of benefits or kindness or benefits to society. Thus, imprisonment is not an absolute in the view of Islamic law. Based on the inventory of customary law as the original unwritten law of the Indonesian nation, no form of imprisonment was found. Therefore, without imprisonment, customary law can be enforced to maintain order and create justice in Indonesian society. From this analysis, especially related to the study of Islamic law and customary law, it is concluded that imprisonment can be considered for abolition if its shortcomings are more dominant than its benefits. Apart from that, the Indonesian Government should provide a forum for the idea of privatizing correctional institutions in the sense that the management of correctional institutions is carried out by private parties on a non-profit basis.